2004
DOI: 10.1249/01.mss.0000132274.26612.23
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphisms Associated with Human Muscle Size and Strength

Abstract: FAMuSS should help identify genetic factors associated with muscle performance and the response to exercise training. Such insight should contribute to our ability to predict the individual response to exercise training but may also contribute to understanding better muscle physiology, to identifying individuals who are susceptible to muscle loss with environmental challenge, and to developing pharmacologic agents capable of preserving muscle size and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 31 publications
1
111
1
2
Order By: Relevance
“…Thus, it appears NOS3 +894 G>T may habitually influence the preference of light PA, vigorous PA and sitting and the strength gains in women that can result from an RT program. These findings suggest NOS3 +894 G>T may be important to consider for a personalized approach to exercise prescription along with a growing number of genetic variants that have been reported to be associated with muscle performance [15,[24][25][26][27] and habitual PA [21,[28][29][30][31][32]. For example, when recommending exercise to adults for its overall health benefits, the NOS3 +894 G>T and PA intensity dependent genotype differences we found could be considered when counseling people to become more physically active due to what appears to be a genetic predisposition to prefer light over vigorous intensity PA among those with the TT genotype.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Thus, it appears NOS3 +894 G>T may habitually influence the preference of light PA, vigorous PA and sitting and the strength gains in women that can result from an RT program. These findings suggest NOS3 +894 G>T may be important to consider for a personalized approach to exercise prescription along with a growing number of genetic variants that have been reported to be associated with muscle performance [15,[24][25][26][27] and habitual PA [21,[28][29][30][31][32]. For example, when recommending exercise to adults for its overall health benefits, the NOS3 +894 G>T and PA intensity dependent genotype differences we found could be considered when counseling people to become more physically active due to what appears to be a genetic predisposition to prefer light over vigorous intensity PA among those with the TT genotype.…”
Section: Discussionmentioning
confidence: 94%
“…We investigated the influence of NOS3 +894 G>T and −786 T>C on habitual PA and the muscle strength response to RT among a large sample of healthy, European-derived American adults from FAMuSS [15]. We found that NOS3 +894 G>T associated with habitual PA and the muscle strength response to RT.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations